Just-in-Time Compound Pooling Increases Primary Screening Capacity without Compromising Screening Quality. (June 2015) - Elkin, L. L.; Harden, D. G.; Saldanha, S.; Ferguson, H.; Cheney, D. L.; Pieniazek, S. N.; Maloney, D. P.; Zewinski, J.; O'Connell, J.; Banks, M.
Compound pooling, or multiplexing more than one compound per well during primary high-throughput screening (HTS), is a controversial approach with a long history of limited success. Many issues with this approach likely arise from long-term storage of library plates containing complex mixtures of compounds at high concentrations. Due to the historical difficulties with using multiplexed library plates, primary HTS often uses a one-compound–one-well approach. However, as compound collections grow, innovative strategies are required to increase the capacity of primary screening campaigns. Toward this goal, we have developed a novel compound pooling method that increases screening capacity without compromising data quality. This method circumvents issues related to the long-term storage of complex compound mixtures by using acoustic dispensing to enable "just-in-time" compound pooling directly in the assay well immediately prior to assay. Using this method, we can pool two compounds per well, effectively doubling the capacity of a primary screen. Here, we present data from pilot studies using just-in-time pooling, as well as data from a large >2-million-compound screen using this approach. These data suggest that, for many targets, this method can be used to vastly increase screening capacity without significant reduction in the ability to detect screening hits.